Receptor for Advanced Glycation End Products (RAGE) and Mechanisms and Therapeutic Opportunities in Diabetes and Cardiovascular Disease: Insights From Human Subjects and Animal Models - Egaña-Gorroño, Lander; López-Díez, Raquel; Yepuri, Gautham; Ramirez, Lisa S.; Reverdatto, Sergey; Gugger, Paul F.; Shekhtman, Alexander; Ramasamy, Ravichandran; Schmidt, Ann Marie (Frontiers in Cardiovascular Medicine, 2020)
Obesity and diabetes are leading causes of cardiovascular morbidity and mortality. Although extensive strides have been made in the treatments for non-diabetic atherosclerosis and its complications, for patients with diabetes, these therapies provide less benefit for protection from cardiovascular disease (CVD). These considerations spur the concept that diabetes-specific, disease-modifying therapies are essential to identify, especially as the epidemics of obesity and diabetes continue to expand. Hence, as hyperglycemia is a defining feature of diabetes, it is logical to probe the impact of the specific consequences of hyperglycemia on the vessel wall, immune cell perturbation and endothelial dysfunction – all harbingers to the development of CVD. In this context, high levels of blood glucose stimulate the formation of the irreversible advanced glycation end products, the products of nonenzymatic glycation and oxidation of proteins and lipids. AGEs accumulate in diabetic circulation and tissues and the interaction of AGEs with their chief cellular receptor, receptor for AGE or RAGE, contributes to vascular and immune cell perturbation. The cytoplasmic domain of RAGE lacks endogenous kinase activity; the discovery that this intracellular domain of RAGE binds to the formin, DIAPH1, and that DIAPH1 is essential for RAGE ligand-mediated signal transduction, identifies the specific cellular means by which RAGE functions and highlights a new target for therapeutic interruption of RAGE signaling. In human subjects, prominent signals for RAGE activity include the presence and levels of two forms of soluble RAGE, sRAGE and endogenous secretory (es) RAGE. Further, genetic studies have revealed single nucleotide polymorphisms (SNPs) of the AGER gene (AGER is the gene encoding RAGE) and DIAPH1, which display associations with CVD. This Review presents current knowledge regarding the roles for RAGE and DIAPH1 in the causes and consequences of diabetes, from obesity to CVD. Studies both from human subjects and animal models are presented to highlight the breadth of evidence linking RAGE and DIAPH1 to the cardiovascular consequences of these metabolic disorders.